Effect of Escherichia Coli on Decorin and Type I Collagen Levels in Fetal Membranes of Premature Balb/c Mice - Nirwan Nugraha; Suheni Ninik Hariyati; Didik Agus Gunawan; Mokhammad Nooryanto; Pande Made Dwijayasa (Asian Journal of Health Research, 2022)
Introduction: Premature birth is a global problem in various countries worldwide. The pathogenesis leading to preterm labor may occur in early pregnancy and is associated with inflammatory pathways and changes in the angiogenic process. Decorin and biglycan are hypothesized to play a role in pregnancy maintenance, wherein preterm delivery, these levels are thought to be reduced. This study was examined effect of Escherichia coli on Decorin and Type I Collagen levels in fetal membranes of Premature Balb/c Mice Methods: There were 28 pregnant Balb/c mice divided into 4 groups, with a post-test-only control group design in true experimental design research. The first control group (N1) was a group of pregnant mice dissected on day-15, while the second control group (N2) were mice pregnant at term followed up to parturition. Group P1 were given Escherichia coli 1x109 CFU/ ml dose on the cervix on day-15, while the second treatment group (P2) were given Escherichia coli in the cervical canal on day-15 followed by delivery. We examined the Decorin and Type I Collagen levels between group. One-way ANOVA was used to analyze the collected data. Results: There was a significant difference in the mean decorin levels between the control group N1 vs P2 (12.35±2.24 ng/mL vs 6.62±1.50 ng/mL; p=0.000). In addition, a significant difference was also found in the mean level of type 1 collagen between the control group N1 vs P2 group (283.5±31.3 ng/mL vs 170.6±38.8 ng/mL; p=0.000). Conclusion: A decrease in decorin levels affects the reduction in collagen type 1 levels in fetal membranes of Balb/C mice in premature models.